PREPARATIONS FOR REMEDIATION OF A FORMER SURFACE MINE – A TECHNICAL RECLAMATION AREA - Petr Černoch; Jiří Košťál (Acta Polytechnica CTU Proceedings, 2019)
The reclamation area for secondary float energy by-products is located on a spoil heap, 45m thick and 30 years old, and consists mostly of clay stone with high plasticity. When depositing a first 18m high stack, it was necessary to verify stability and to analyse deformations during the reclaiming operation. Stability and deformation depend on the shallow groundwater level. Therefore, it was necessary to propose a technical solution for drainage of the structure concerned. This can be divided into two parts: drainage of surface water and drainage of the shallow underground water. It means a complex solution for the entire construction that would not be possible without long-term monitoring of the construction and field mapping. Completion of the proposed facilities will increase the stability of the reclamation area and it will then be possible to continue with remediation of the former surface mine.